Metastatic Melanoma of Uncertain Primary with 5-Year Durable Response after Conventional Therapy: A Case Report with Literature Review - Jomjit Chantharasamee; Jitsupa Treetipsatit (Case Reports in Oncological Medicine)
A 51-year-old Thai woman presented with bilateral leg edema and painful left inguinal mass for 6 months. Physical examination revealed matted bilateral inguinal lymph nodes up to 9 cm in size. Otherwise, physical examinations including skin were unremarkable. The result of the lymph node incisional biopsy is consistent with that of metastatic melanoma. The extensive investigation demonstrated multiple intra-abdominal and inguinal lymph nodes without detectable primary tumor. Palliative radiation and conventional chemotherapy were prescribed. The CT scan between treatments showed that the response was stable disease, but the following CT scan demonstrated a gradual decrease in size from August 2012 to November 2017 including the lesions outside radiation fields. Moreover, she developed vitiligo during a follow-up visit. The previous data reported the median overall survival among the patients who were treated with conventional chemotherapy ranging from 9.1 to 9.3 months and whose 5-year survival was less than 10%. This case represented a metastatic melanoma of unknown primary who achieved a durable response by conventional treatment. The clinical features including nodal-only disease, vitiligo, and abscopal effect of radiation were considered to be the favorable factors.